Green Historiography in Indonesia: Evolution and Adaptation of Environmental History - Hutagalung, Albertus; Erniwati, Erniwati; Patra, Haldi; Mulyani, Fini Fajri (Analisis Sejarah, 2025)
This study examines the evolution of environmental history as a historiographical response to the global ecological crisis and the limitations of anthropocentric approaches in conventional history writing. It seeks to understand how the global development of environmental history has influenced the direction, methodology, and character of its adaptation in Indonesia. Using a qualitative and reflective literature-based method with a comparative historiographical approach, this article analyzes key global works, primarily from the United States and Europe. It compares them with Indonesian scholarship to trace the trajectory of this emerging field. The findings reveal that while Indonesia possesses a rich ecological past, environmental historiography remains underdeveloped due to the limited availability of ecological primary sources, the dominance of socio-economic paradigms, and the absence of specialized academic platforms. Nevertheless, works by scholars such as Peter Boomgaard demonstrate that environmental history provides a critical lens for reinterpreting the interaction between power, society, and nature within colonial and postcolonial contexts. The study concludes that environmental history can serve as both a theoretical and methodological alternative to mainstream Indonesian historiography. It promotes a green historiography that integrates ecological perspectives into national history, enriches historiographical debates, and contributes to sustainability through eco-pedagogy and interdisciplinary collaboration.